Pengaruh Budaya Organisasi, Kedisiplinan, Kepemimpinan dan Beban Kerja terhadap Kinerja Karyawan - Galuh Setyo Pamungkas; Sulistyowati Sulistyowati; Roesjanto Roesjanto (Indonesian Maritime Researchers and Lecturers, 2025)
This research aims to analyze the partial and simultaneous influence of Organizational Culture (X_1), Discipline (X_2), Leadership (X_3), and Workload (X_4) on Employee Performance (Y) at PT. PELINDO III (Persero) Tanjung Emas Branch Semarang. Utilizing a quantitative associative approach, data were collected from 50 employee respondents and analyzed using multiple linear regression. The analysis confirmed that X_1, X_2, and X_3 positively and significantly influence Employee Performance, while Workload (X_4) significantly influences performance negatively (β = -0.091). Organizational Culture (X_1) was identified as the most influential factor (β = 0.461), followed by Leadership (X_3, β = 0.313) and Discipline (X_2, β = 0.149). The results highlight the critical need for a strong organizational culture and effective leadership in overcoming the inevitable challenges posed by workload pressure in the demanding port environment. The model demonstrated a strong fit, explaining approximately 68.5% of the variation in Employee Performance. Managerial implications suggest prioritizing culture reinforcement and leadership development to mitigate the negative impact of high operational workload.